A study of selected community parish archives practices - Robles, S. Ma. Bernardita L. (Institute of Library and Information Science, University of the Philippines Diliman, 2005)
Archives are needed as the primary source of identity and information of the past which continue to affect human rights. The value of an archives is its accessibility. The archives, as ministry of evangelization in today's church, promotes the use of its resources to strengthen spiritual lives and provide accurate documentation of the historical church. The voluminous collection of archival documents of the Philippine Church, particularly the parishes, are seemingly neglected and unattended. More importantly, the loss of records, whether diocesan or parochial, undermines, religious heritage.